Efektivitas Teknik Shaping dalam Membentuk Perilaku Tepat Waktu pada Mahasiswa yang Sering Terlambat Masuk Kelas - lisa Rahma; Endang Setianingsih (Edupreneurship: Jurnal Pendidikan Ekonomi, 2026)
Punctuality is a crucial aspect of academic discipline that significantly influences the quality of the learning process. However, the phenomenon of students arriving late to class remains a common issue in higher education settings. This study aims to examine the effectiveness of shaping techniques in developing punctual behavior among university students who frequently arrive late to class. Shaping is a behavioral approach that involves reinforcing successive approximations toward a target behavior. This research employed a single-subject experimental design (A-B-A) involving three university students identified as having chronic tardiness behavior. The intervention was conducted over eight sessions, with data collected through direct observation and self-monitoring. The results showed a significant reduction in lateness frequency and duration following the intervention, with all subjects demonstrating consistent punctual behavior by the end of the program. The subjects reported increased self-awareness and motivation to maintain punctuality. This study concludes that shaping techniques are effective in developing punctual behavior among university students and can serve as an alternative intervention for addressing academic discipline issues in higher education institutions.